2020
DOI: 10.1089/jpm.2019.0169
|View full text |Cite
|
Sign up to set email alerts
|

Hospital and Health System Policies Concerning the California End of Life Option Act

Abstract: Background: The End of Life Option Act (EOLOA) legalized physician aid in dying for competent, terminally ill Californians in 2016. The law allows clinicians, hospitals, and health systems to decide whether to participate. About 4 in 10 California hospitals permit the EOLOA, but little is known about their approaches and concerns. Objective: Describe hospital EOLOA policies and challenges. Design and Measurements: Survey study of hospitals in California, administered September 2017 to March 2018. We describe h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In Switzerland, where assisted dying has occurred only in right-to-die organizations until very recently (Bloom 2022, Gandsman 2018, Richards 2016, the role of organized medicine has shifted over time in an incremental move toward incorporating assisted death into medical institutions (Stavrianakis 2020). In a survey of 270 California hospitals conducted between September 2017 and May 2018 regarding their policies on the End of Life Option Act, Cain et al (2020a) found that most (87%) had adopted formal policies on physicians' participation, whether or not they permitted it. Of these, 39% permitted staff physicians to write prescriptions, and 61% prohibited physicians from writing prescriptions.…”
Section: Implementation and Regulation As Bureaucratic Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…In Switzerland, where assisted dying has occurred only in right-to-die organizations until very recently (Bloom 2022, Gandsman 2018, Richards 2016, the role of organized medicine has shifted over time in an incremental move toward incorporating assisted death into medical institutions (Stavrianakis 2020). In a survey of 270 California hospitals conducted between September 2017 and May 2018 regarding their policies on the End of Life Option Act, Cain et al (2020a) found that most (87%) had adopted formal policies on physicians' participation, whether or not they permitted it. Of these, 39% permitted staff physicians to write prescriptions, and 61% prohibited physicians from writing prescriptions.…”
Section: Implementation and Regulation As Bureaucratic Practicesmentioning
confidence: 99%
“…Physicians play an important gatekeeping role, declining to participate if they do not think the patient meets the eligibility criteria (Buchbinder 2022, de Andrade Neves 2020, Pool 1995. Although stringent regulations reassure physicians that they are acting lawfully (Sellars et al 2022), physicians must adjudicate eligibility with few formal training opportunities, and with many ambiguities in the legal protocol (Buchbinder et al 2019, Byrnes et al 2022, Cain et al 2020a, Sellars et al 2022, Winters et al 2022. A study of psychiatrists in the Netherlands found that differentiating between suicidality and "rational death wishes" required a great deal of skill and that Dutch laws do not fully appreciate the nuances between different forms of suffering (Pronk et al 2021).…”
Section: Implementation and Regulation As Bureaucratic Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this progress, California hospitals and health systems still experienced challenges with newly legalized MAID. [17][18][19][20][21] Legalization in Victoria (Australia) came into effect in mid-2019. With an 18-month implementation period, academic literature addressing operationalization and training became available synchronously.…”
Section: Introductionmentioning
confidence: 99%